2011
DOI: 10.1021/np200035m
|View full text |Cite
|
Sign up to set email alerts
|

Marianins A and B, Prenylated Phenylpropanoids from Mariannaea camptospora

Abstract: Marianins A (1) and B (2), two new prenylated phenylpropanoids, were isolated from the culture extract of the fungus Mariannaea camptospora. Structures of marianins were elucidated by interpretation of NMR and other spectroscopic data. 1 is a 5-methylcoumarin bearing two prenyloxy groups, while 2 is an orcinol derivative substituted with a 3,3-dimethyl-4-pentenoyl chain. 2 is possibly derived from 1 through a Claisen rearrangement of the prenyl group, followed by lactone hydrolysis and decarboxylation. These c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
(15 reference statements)
1
11
0
Order By: Relevance
“…The NMR data (Table 2) suggested that the structure of compound 5 was likely an amino-acid ester, which was similar to that of asperphenamate (Fukuda et al 2011). The difference between the two compounds was that an additional hydroxyl group was located at 5 .…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The NMR data (Table 2) suggested that the structure of compound 5 was likely an amino-acid ester, which was similar to that of asperphenamate (Fukuda et al 2011). The difference between the two compounds was that an additional hydroxyl group was located at 5 .…”
Section: Resultsmentioning
confidence: 59%
“…Its molecular formula was determined to be C 16 H 18 O 6 with m/z 307.1172 [M + H] + (calcd for C 16 H 19 O 6 , 307.1176) based on HR-ESI-MS data. Analyses of the 1 H, 13 C NMR data (Table 1) and HSQC spectra of 7 indicated that it belongs to isopentenylcoumarin (Fukuda et al 2011), which was bearing substituent groups of methylol, methoxy, and hydroxyl. The prenyloxy group was attached to C-5 by the analysis of HMBC correlations (Figure 3) from H 2 -11 to C-5 (δ 149.2).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] They show diverse biological and pharmacological activities ranging from antimicrobial, anti-arrhythmic, antitumor, antifungal, anti-HIV, anti-osteoporosis to anti-inflammatory. [5][6][7][8][9][10][11][12] Apart from their pharmaceutical applications, [13][14] coumarins have been used as additives in foods, perfumes and cosmetics as well as in the preparation of optical brighteners, laser dyes, fluorescent labels and nonlinear optical chromophores.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial assay 16 and cytotoxic assay 17 were carried out according to the procedures previously described.…”
mentioning
confidence: 99%